Suffolk, ss. At the Superior Court, &c. August [blank] 1774 : whereas the Honourable Peter Oliver, Esq ; chief justice of this court, stands charged and impeached of divers high crimes and misdemeanors, and more especially with bribery and corruption in his said office ... we hereby testify before God and the world, our sentiments in the premises, and refuse acting as grand jurors at this court ... Witness our hands ([Printed by Edes and Gill], 1774)
Grand Jury refusal for members to be impaneled with Judge Peter Oliver presiding. The jury listed their objections, which included the impeachment of Oliver for high crimes and misdemeanors.